2021
DOI: 10.1126/sciadv.abg3750
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of spatial architecture in primary liver cancer

Abstract: Spatial transcriptome technique was applied to decipher the spatial architecture and TME characteristics of liver cancers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(192 citation statements)
references
References 67 publications
(104 reference statements)
5
144
0
1
Order By: Relevance
“…Given the limits of tissue samples, we further performed a secondary data analysis on a previous study of ST sequencing on primary liver cancers, which also presented spatial transcriptome map of three major liver cancer subtypes 23 . In order to better match the spatial location of our tissue samples with higher spatial continuity that includes the carcinoma, fiber cord sector to para-carcinoma sector, we chose the leading-edge section of 4 HCC samples from their ST data and annotated them as HCC1, HCC2, HCC3, and HCC4 ( Figure S2 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the limits of tissue samples, we further performed a secondary data analysis on a previous study of ST sequencing on primary liver cancers, which also presented spatial transcriptome map of three major liver cancer subtypes 23 . In order to better match the spatial location of our tissue samples with higher spatial continuity that includes the carcinoma, fiber cord sector to para-carcinoma sector, we chose the leading-edge section of 4 HCC samples from their ST data and annotated them as HCC1, HCC2, HCC3, and HCC4 ( Figure S2 A).…”
Section: Resultsmentioning
confidence: 99%
“…ST was first applied in the mouse brain and human breast cancer to verify the feasibility of spatial visualization and quantitative analysis of gene expression 15 ; it was then used to explore the spatial discrepancy of gene expression in dynamic disease processes, such as amyotrophic lateral sclerosis 16 and Alzheimer's disease 17 , as well as in normal tissue development processes 18 . Moreover, ST is conducive to resolving spatial heterogeneity and spatial gene expression patterns in various tumors, such as prostate cancer 19 , melanoma 20 and pancreatic ductal adenocarcinoma 21 , and primary liver cancer 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution spatial transcriptomes of PLCs were constructed by scRNA-seq to reveal the extensive global and local intratumor heterogeneities of tumors and TMEs ( 115 ). It was reported to be the first study to analyze the genome-wide TME characteristics from normal to leading-edge to tumor regions, identifying the vital role of complete fibrous capsule for both TME architecture and intratumor heterogeneity.…”
Section: Applications Of Single-cell Sequencing In Liver Cancermentioning
confidence: 99%
“…Wu et al. progressively compared the spatial TME characteristics from nontumor to leading-edge to tumor regions, demonstrating that the tumor capsule potentially affected intratumor spatial cluster continuity, transcriptome diversity, and immune cell infiltration ( 115 ). Their results revealed that the integrity of the capsule was closely related to the distribution of their surrounding stromal and immune cells but had few effects on the activities of hallmark pathways in neither normal nor tumor regions.…”
Section: Applications Of Single-cell Sequencing In Liver Cancermentioning
confidence: 99%
“…However, more effort is necessary to identify the specific mechanism. Additionally, recent excellent work- based spatial transcriptomics technology has revealed intense contact between LCSCs and vascular infiltration, which also seems to suggest a robust relationship between the two components [ 86 ]. Together, more evidence from several novel technologies, such as spatial and single-cell transcriptomics, might provide more awareness and inspiration about the topic.…”
Section: The Tme and Liver Cancer Stemness Maintenancementioning
confidence: 99%